Водные, подземные и небесные олени сихиртя - Laptander, Roza (Institute of Linguistic research, Russian Academy of Science, 2019)
The Sikhirtya (Nenets:сихиртя) were mythical people who lived in the tundra before the Nenets. According to legends, the Sikhirtya were small people, wearing beautiful clothes with metal pendants. They lived underground, inside of tall sandy hills and came out to the surface of the tundra at night or in the mist. The folklore image of Sikhirtya has mythologically imprinted features of the real people. According to the archaeological data, the predecessors of the Nenets were not involved very much into reindeer herding work but engaged in hunting to wild reindeer, sea mammals, and fishing. In this article, the author analyses one Nenets legend about the Sikhirtya and their mythological reindeer.